Nucleotide selection by the Y-family DNA polymerase Dpo4 involves template translocation and misalignment. Issue 4 (21st November 2013) - Brenlla, Alfonso; Markiewicz, Radoslaw P.; Rueda, David; Romano, Louis J.
Abstract: Y-family DNA polymerases play a crucial role in translesion DNA synthesis. Here, we have characterized the binding kinetics and conformational dynamics of the Y-family polymerase Sulfolobus solfataricus P2 DNA polymerase IV (Dpo4) using single-molecule fluorescence. We find that in the absence of dNTPs, the binary complex shuttles between two different conformations within ∼1 s. These data are consistent with prior crystal structures in which the nucleotide binding site is either occupied by the terminal base pair (preinsertion conformation) or empty following Dpo4 translocation by 1 base pair (insertion conformation). Most interestingly, on dNTP binding, only the insertion conformation is observed and the correct dNTP stabilizes this complex compared with the binary complex, whereas incorrect dNTPs destabilize it. However, if the n+1 template base is complementary to the incoming dNTP, a structure consistent with a misaligned template conformation is observed, in which the template base at the n position loops out. This structure provides evidence for a Dpo4 mutagenesis pathway involving a transient misalignment mechanism.